The Impact Of Economic Freedom On Economic Growth: Cross-Sectional Study For The Year 2019 - Maouchi, Imad (Journal of Human Sciences, 2023)
Economic growth is considered one of the important indicators for evaluating the economic performance of countries, due to its distinctive features in its calculation and it is more expressive of the economic situation of countries,Through this research paper, we took one of the two workers to test them in a econometric model with cross-sectional data for 174 countries for the year 2019,They were represented in both economic freedom and the ease of doing business, as the data is segmental and the heterogeneity that results from it in the systems of the studied countries, the index of ease of doing business was inconsistent with economic theory, as its effect appeared to be reversed. As for economic freedom, it appeared that it positively affects economic growth.